Understanding the creative economy : a tale of two cities clusters - Keane, Michael (Intellect Ltd, 2009)
This article investigates underlying constraints within China’s creative economy. Drawing on two studies of creative clusters in Suzhou and Foshan, it identifies the importance of knowledge transfer and internationalization to the generation of higher value-added products and services. Both examples illustrate relationships between resources, activities, routines and entrepreneurship. The article argues that the examples notwithstanding, the vast majority of what is accounted for in data collection as China’s creative industries are more appropriately cultural industries. The focus on cultural industries drives local development and increases land values but the benefits are rarely dispersed internationally or into the broader economy.